Effect of Lowering Diastolic Pressure in Patients With and Without Cardiovascular Disease: Analysis of the SPRINT (Systolic Blood Pressure Intervention Trial). Issue 5 (May 2018) - Khan, Nadia A.; Rabkin, Simon W.; Zhao, Yinshan; McAlister, Finlay A.; Park, Julie E.; Guan, Meijiao; Chan, Sammy; Humphries, Karin H.
Abstract : Systolic and diastolic blood pressure thresholds, below which cardiovascular events increase, are widely debated. Using data from the SPRINT (Systolic Blood Pressure Intervention Trial), we evaluated the relation between systolic and diastolic pressure and cardiovascular events among 1519 participants with or 7574 without prior cardiovascular disease. Using Cox regression, we examined the composite risk of myocardial infarction, other acute coronary syndrome, stroke, heart failure, or cardiovascular death, and follow-up systolic and diastolic pressure were analyzed as time-dependent covariates for a median of 3.1 years. Models were adjusted for age, sex, baseline systolic pressure, body mass index, 10-year Framingham risk score, and estimated glomerular filtration rate. A J-shaped relationship with diastolic pressure was observed in both treatment arms in patients with or without cardiovascular disease ( P nonlinearity⩽0.002). When diastolic pressure fell <55 mm Hg, the hazards were at least 25% higher relative to 70 mm Hg ( P =0.29). The hazard ratios (95% CI) of diastolic pressure <55 mm Hg versus 55 to 90 mm Hg were 1.68 (1.16–2.43), P value 0.006 and 1.52 (0.99–2.34), P value 0.06 in patients without and with prior cardiovascular disease, respectively. After adjusting for follow-up diastolic pressure, follow-up systolic pressure was not associated with the outcome in those without prior cardiovascular disease ( P =0.64). In those with cardiovascular disease, adjusting for diastolic pressure, follow-up systolic pressure was associated with the risk in the intensive arm (hazard ratio per 10 mm Hg decrease, 0.86; 95% CI, 0.75–0.99; P interaction=0.02). Although the observed J-shaped relationship may be because of reverse causality in the SPRINT population, we advise caution in aggressively lowering diastolic pressure. Abstract : Supplemental Digital Content is available in the text.